Peran dan Fungsi Komite Sekolah dalam Meningkatkan Mutu Pendidikan - M. Misbah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Indonesian government reformation affected changing paradigm, from centralization to decentralization, that evident from real and broad autonomy by local government to manage and improve their territory, include education management. The realization is emergence Dewan Pendidikan (education board) at district level and Komite Sekolah (school committee) at education unit level. This enhances community direct involvement to education domain. School committee have role as advisory agency, supporting agency, controlling agency, also as mediatory agency. Therefore, school committee must cooperate with community and government to run quality education.Â